The Boundless Classroom : Designing Purposeful Instruction for Any Learning Environment - Lang, Nathan D.; Witty, James Vince (Book collections on Project MUSE., 2022)
"A global pandemic hit our world, and education has forever changed. But have your instructional practices changed? Teachers must now leverage technology to provide students with high-quality teaching and learning experiences that transcend a traditional classroom's walls. This is a historic opportunity to abandon antiquated teaching practices and reimagine instruction in ways that boost learning outcomes and prepare students for living and working in the digital age. This book offers guidance for creating and sustaining rigorous and engaging blended learning solutions. Opening with lessons learned from the pandemic, the book addresses impacts on lesson design and delivery, student engagement, assessment, and teacher training and PD. The following chapters build on and address these experiences, with each chapter featuring practical examples on how to implement effective blended instructions as well as examples from the field to illustrate effective approaches to blended and online instruction"--